The acceptance of gamified smart tourism application: mobile augmented reality in Malaysia's tourism - Johar, Muhammad Izzat; Saad, Mazni (2019)
The current travelling and visitation method are needing a change or else, the sustainability of tourism of a place would face serious consequences. The adoption of technology was rather slow to be implemented as stakeholders and businesses hesitate to take risks and gave unrealistic goals and expectations despite not having enough literacy on the subject such as the usage of gamified smart tourism application. This study empirically investigates what factors aﬀect the acceptance of smart tourism applications that incorporate game elements, using Google Maps Local Guide program and augmented reality games that use geocaching as an example application. As an initial approach, it is incorporated with diverse theoretical approaches: perceived usefulness; perceived ease of use; and perceived enjoyment from technology acceptance model. Regression and Pearson Correlation were used as an analysis tool using IBM-SPSS. Results from 40 total respondents obtained shows that while the acceptance is achieved, not all the studied variables were significant. The perceived usefulness and enjoyment have a strong positive relationship towards the acceptance of gamified smart tourism application while the perceived ease of use did not.